Expression and clinical significance of matrix metalloproteinase-9 in lymphatic invasiveness and metastasis of breast cancer. - Qiu-Wan Wu; Qing-Mo Yang; Yu-Fan Huang; Hong-Qiang She; Jing Liang; Qiao-Lu Yang; Zhi-Ming Zhang (PLoS ONE, 2014)
BACKGROUND: Matrix metalloproteinase 9 (MMP-9) is a type-IV collagenase that is highly expressed in breast cancer, but its exact role in tumor progression and metastasis is unclear. METHODS: MMP-9 mRNA and protein expression was examined by real-time reverse transcriptase PCR and immunohistochemical staining, respectively, in 41 breast cancer specimens with matched peritumoral benign breast epithelial tissue and suspicious metastatic axillary lymph nodes. Lymph vessels were labeled with D2-40 and lymphatic microvessel density (LMVD) was calculated. Correlation of MMP-9 protein expression with clinicopathological parameters and LMVD was also evaluated. RESULTS: MMP-9(+) staining in breast cancer specimens (35/41, 85.4%) was higher than in matched epithelium (21/41, 51.2%; P<0.05) and lymph nodes (13/41, 31.7%; P<0.001). Higher MMP-9 mRNA expression was also detected in tumor specimens compared with matched epithelial tissues and lymph nodes (P<0.05). Elevated MMP-9 expression was correlated with lymph node metastasis and LMVD (P<0.05). CONCLUSION: MMP-9 was overexpressed in breast cancer specimens compared with peritumoral benign breast epithelium and lymph nodes. Moreover, its expression in the matched epithelium and lymph nodes was positively associated with lymph node metastasis, and its expression in lymph nodes was positively associated with lymphangiogenesis in breast cancer. Thus, MMP-9 is a potential marker for breast cancer progression.